Molecular characterization of porcine circovirus 2 circulating in Assam and Arunachal Pradesh of India. Issue 2 (3rd April 2023) - D'silva, Ajai Lawrence; Bharali, Arpita; Buragohain, Lukumoni; Pathak, Dinesh C.; Ramamurthy, Narayan; Batheja, Rahul; Mariappan, Asok Kumar; Gogoi, Sophia M.; Barman, Nagendra Nath; Dey, Sohini; Chellappa, Madhan Mohan
Abstract: PCV2 is the primary etiological agent of porcine circovirus-associated diseases (PCVADs) which affect pigs worldwide. Currently, there is a worldwide genotype prevalence switch from PCV2b to PCV2d, which has led to increased virulence of the circulating virus strains leading to vaccine failures and selection pressure. In the present study, the PCV2 genotypes circulating in north eastern region (NER) of India particularly the states of Assam and Arunachal Pradesh was characterized by isolation, sequencing and phylogenetic analysis of cap gene. The phylogenetic analysis revealed that the PCV2 isolates circulating in pigs of Assam and Arunachal Pradesh were mostly of PCV2d genotype. Hence, it can be concluded that PCV2d genotype is the most dominating genotype in NER and priority should be given to this genotype for development of future vaccine candidate against PCV2 in India.